A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae) - Sabella, Giorgio; Amore, Elena; Nicolosi, Giuseppe (Zootaxa, 2019)
A new troglobitic Pselaphinae, Tychobythinus villasmundi sp. nov., is described from Villasmundo Cave (Melilli, Syracuse province, Sicily). Major diagnostic features are illustrated based on both male and female specimens. The new species shows some adaptations to cave life, such as pale brown colour, setation consisting of long and flattened setae and suberect shorter setae, absence of wings, anophthalmy, and elongated legs and antennae. It can be easily separated from the related taxa by the different structure of the aedeagus. Tychobythinus villasmundi sp. nov. is known only from Villasmundo Cave, a limestone cave in the south-eastern Sicily.